Соціопрагматика комунікативного простору туризму - Климко, І. Г.; Климко, И. Г.; Кlimkо, I. G. (My University, 2017)
Соціопрагматика подорожі – це її семіотичний, образний та символічний контекст у семіологічному розумінні. Дорогу як культурну цілісність і певний артефакт культури можно уявити як дискурс, «промову подорожі», або як низку співскладених дискурсів. Феномен соціопрагматики, який у лінгвистиці характеризує орентацію на дієвість тексту, а ширше – на театрологію тексту, у статті презентується як театрологія подорожі. Як відомо, театралогія стає однією з провідних інтерпретант культури. Дорогу теж можна представити як певний текст, що сповнений знакових структур. Театрологія текстуальної цілісності подорожі – це театральна інтерпретація знакових структур дороги. Так, соціопрагматика як постлінгвістичний феномен набуває свого семіотичного та культурологічного виміру у вимірі туристичної діяльності та інших практик подорожування. Театрологію дороги презентує код поведінки в подорожі як певна ігрова цілісність уходу, подорожування та повернення додому.

Социопрагматика путешествия – это семиотический, образный и символический контекст в семиологическом понимании. Дорогу как культурную целостность и определенный артефакт культуры можно представить как дискурс, «речь путешествия», или как ряд соположенных дискурсов, которые в лингвистике характеризуют орентацию на действенность текста, а шире – на театрологию текста, в нашему случае на театрологию путешествия. Театрология становится одной из ведущих интерпретант культуры. Дорогу также можно представить как определенный текст, который преисполнен знаковых структур. Театрология текстуальной целостности путешествия – это театральная интерпретация знаковых структур дороги. Социопрагматика как постлингвистический феномен приобретает свои семиотические и культурологического измерения в контексте туристической деятельности и других практик путешествия. Театрологию дороги репрезентирует код поведения в путешествии как определенная игровая целостность ухода, путешествия и возвращения домой.

Sotioprogmatics of a trip – it her semiotic, vivid and symbolic context in the semiologic understanding. The road as a cultural integrity and certain artefact of culture cfn be presented as a discourse, literally “speech of trip”, or as a row of half folded discourses where this phenomenon of sotioprogmatics, that characterizes the orientation to the validity of the text in linguistics, and wider – to the theatrology of text, in our case on a theatrology of a trip. As known, the theatrology becomes one of the leading determinant of culture. A road too can be presented as certain text that is full of sign structures. Тhe theatrology of textual integrity of trip is a theatrical interpretation of sign structures of the road. Yes, the sotioprogmatics as a post-lin-guistic phenomenon acquires the semiotic and culturological measuring in measuring of tourist activity and other practices of trip. Тhe theatrology of the road is represented by the code of behavior in a trip as a playing integrity of leaving, a trip and coming home. A road gives possibilities to be another: liberated, relaxed, to wish opening new round itself, new in itself. A situation of trip in the plan of it’s sotioprogmatics is anequivalent enough and relevant, it repeats in different variations, in the different forms of trip, in different tourist actions. And the last configuration of trip is arrival to the new house, when people adapt oneself to the new dwelling, that too determine within the framework of ritualization. People who come on set time in a new house, are determined as guests. When they return home from the military service, from a distant trip, they too set time understand themselves as guests. Yes, a guest status after service proceeds even two months, a fellow does not go to work, they have a rest as though.
Климко І. Г. Соціопрагматика комунікативного простору туризму / І. Г. Климко // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 17. - С. 55-58.
Keywords: культура; дорога; шлях; соціопрагматика подорожі; театрологія подорожі; культура; дорога; путь; социопрагматика путешествия; театрология путешествия; culture; road; way; sotioprogmatics of a trip; theatrology of a trip